The effects of foliar amino acid and Zn applications on agronomic traits and Zn biofortification in soybean (Glycine max L.) - Han, Şule; Sönmez, İlker; Qureshi, Moin; Güden, Birgül; Gangurde, Sunil S.; Yol, Engin (Frontiers in Plant Science, 2024)
The production and consumption of soybeans are widespread due to their nutritional and industrial value. Nutrient enrichment is vital for improving the nutritional quality of soybeans. This study aimed to evaluate the effect of foliar application of amino acids (AA) and zinc (Zn) on agronomic traits and the accumulation of grain Zn in soybeans. The experimental design comprised 16 treatment combinations involving four levels of amino acid application (0, 50, 100, and 150 ml 100 L-1) and Zn (0, 2, 4, and 6 mg L-1) following a randomized complete block design with three replications in field conditions. The results demonstrated that the application of foliar Zn and AA did not affect the yield, whereas that of AA50*Zn2 and AA150*Zn2 affected the number of pods and branches. The effects of AA application on N and the protein content in grains were determined to be significant. The application of AA100*Zn6 emerged as the most effective treatment for the enhancement of Zn biofortification in soybean grains. The combined foliar application of AA and Zn contributed to enhanced Zn accumulation in the grains.